Profile of Rhinosinusitis Patients with Orbital Complications at the Ear, Nose, and Throat (ENT) Outpatient Unit, Dr. Soetomo General Academic Hospital, Surabaya, from January 2015 to April 2022 - Putri, Made Ayu Rheina; Sutikno, Budi; Primitasari, Yulia; Nugroho, Puguh Setyo (Universitas Airlangga, 2025)
Highlights: Most rhinosinusitis patients with orbital complications were diagnosed as chronic rhinosinusitis. Orbital cellulitis (Chandler II) was the most common orbital complication degree. Rhinosinusitis patients with orbital complications commonly experience eye pain, swollen eyes, and persistent runny noses. Abstract Introduction: Rhinosinusitis is an inflammation of the mucosa of the nasal cavity and/or paranasal sinuses. The most common complication is orbital. The limited data available does not account for the high number of cases of rhinosinusitis. This study examined the profile of rhinosinusitis patients with orbital complications. Methods: This was an observational descriptive study with a retrospective design. It used secondary data from medical records of patients with rhinosinusitis and orbital complications at the Ear, Nose, and Throat (ENT) Outpatient Unit, Dr. Soetomo General Academic Hospital, Surabaya, from January 2015 to April 2022. Results: There were 40 samples that met the inclusion and exclusion criteria (n=40). As many as 80% of cases were chronic rhinosinusitis, and 20% were acute. The average age of chronic rhinosinusitis was in 6th decade, while acute rhinosinusitis (ARS) was in 3rd decade. The majority of patients were males and reside outside Surabaya. Signs and symptoms that ARS patients often experienced were eye pain and swelling, nasal congestion, persistent runny nose, and decreased vision. Meanwhile, chronic rhinosinusitis included eye swelling and pain, persistent runny nose, and facial pain. The most common Chandler’s degree was orbital cellulitis (Chandler II). The most common treatment for ARS was a combination of medicamentosa and non-medicamentosa or medicamentosa and surgery, while chronic rhinosinusitis was a combination of medicamentosa, non-medicamentosa, and surgery. Conclusion: There were outcome differences between patients with acute and chronic rhinosinusitis regarding age, manifestations, and treatments, but there were similarities in sex, domicile, and Chandler’s degree predominance.